Ayurvedic Approach for Management of (Hemorrhagic Ovarian Cyst) Andashayagata Raktaja Granthi – A Case Report - Bhargava, Nikita; Bharathi, K; Choudhary, Poonam; Jangid, Pooja (International Research Journal of Ayurveda & Yoga, 2024)
Ovarian cysts can be either simple or complicated. Complex ovarian cysts contain either a solid or blood component. A common worry in standard gynecological care is ovarian cystic masses. The findings show that there are wide variations in the prevalence of ovarian cysts. Reports state that 8–18% of post-menopausal and pre-menopausal women have ovarian cysts. Most cysts are asymptomatic and can only be detected by routine ultrasonography. Certain ones are very symptomatic, posing challenges for women in their day-to-day activities. The symptoms are significantly influenced by the size of the cysts. A closed, sac-like structure on or inside the ovary that is filled with a liquid or semi-solid material is called an ovarian cyst. A type of functional cyst known as a hemorrhagic cyst is often referred to as a corpus luteal cyst. Treatment options for cysts that do not go away after 3 months include surgery and a combination of oral contraceptive tablets. The need for alternative kinds of management is increasing as a result of the many adverse effects of oral contraceptives, especially for individuals who would rather not have surgery. Treatment for a 22-year-old female patient who had a complicated right ovarian hemorrhagic cyst with dyspareunia, burning micturition, and significant lower abdominal pain was based on Ayurvedic principles. For one and half months, the patient was administered Gandharva Hastadi Tail, Kachnara Gugglu, Arbudhara Kwatha katuki Churna, Chandanasava, Amrutoz, Dhatriloha, and Sankha Bhasm. A follow-up USG revealed that the hemorrhagic cyst had completely disappeared and that the symptoms had much decreased. The current study highlights how Ayurveda can help control ovarian cysts in a way that is beneficial.